IMPLEMENTASI PERATURAN MENTERI KESEHATAN NOMOR 492/MENKES/PER/IV/2010 TENTANG PERSYARATAN KUALITAS AIR MINUM DI KECAMATAN TAMPAN KOTA PEKANBARU - Khairul Fajri; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Needs of the community will be decent and safe drinking water to be consumed every day while increasing the availability of water of drinkable quality and assured in terms of health is increasingly difficult to obtain. Then in anticipation of an unfit drinking water consumption and cause illness then the Government through the Ministry of Health issued a Permenkes Number 492/Menkes/Per/IV/2010 regarding the requirements of the quality of drinking water. Based on Permenkes Number 492/Menkes/Per/IV/2010 about drinking water Quality Requirements also explained that any organizer of a compulsory guarantee drinking water drinking water produced is safe for health. The drinking water is safe for public health if it meets the requirements of purity, chemical physics, radioactive and contained in the mandatory parameters and additional parameters. Mandatory parameter is the quality of the drinking water requirements that must be followed and adhered to by all organizers of drinking water. The organizers also included drinking water that is in the city of Pekanbaru. The purpose of this research is to know the Implementation Permenkes Number 492/Menkes/Per/IV/2010 about drinking water Quality Requirements in the Handsome city of Pekanbaru.The concept used is the theory which includes communication, resources and disposition. To analyse the implementation of the regulation of the Minister of health the number 492/Menkes/Per/IV/2010 about drinking water Quality Requirements in the Handsome city of Pekanbaru, researchers using theory of this Research method using Sugiyono research with qualitative studies are descriptive. In data collection, the author uses interview techniques, observation, and documentation. By using key informant as a source of information and as a source of triangular technique in testing the validity of the data.The results of this research show that the pengimplementan regulations the Minister of health does not run fully in accordance with existing regulations. In the implementation of the regulation of the Minister of health is still to occur irregularities in the process of its implementation. As for the fakotr – a barrier factor in the implementation of the regulation of the Minister of health, namely the lack of communication between the Office of the manufacturer related to the depot drinking water.Keywords: Implementation, Permenkes, Drinking Water Quality Requirements